TMOD-06. HIGH INCIDENCE OF TUMORS AFTER TREATMENT WITH A DNA-ALKYLATING AGENT IN MOUSE STRAINS COMMONLY USED IN PRE-CLINICAL STUDIES. (5th November 2018) - Irtenkauf, Susan; Hasselbach, Laura; Transou, Andrea; Poisson, Laila; Noushmehr, Houtan; Rybkin, Igor; deCarvalho, Ana
Abstract: Glioblastoma (GBM) is commonly treated with the DNA-alkylating agent temozolomide (TMZ). Silencing O6-methylguanine-DNA methyltransferase (MGMT) by promoter hypermethylation predicts response to TMZ. Oral TMZ administration also affects tissues with low MGMT expression, such as bone marrow, resulting in high incidence of leukopenia and secondary leukemia in humans. Here we assessed the anti-tumor effect of TMZ in a panel of orthotopic GBM patient-derived xenografts (GBM-PDXs), and looked for evidence of secondary malignancy in the GBM-PDX lines with extended survival post-TMZ treatment, and also examined TMZ-treated naïve mice from two immunocompromised strains. First, a panel of 12 orthotopic GBM-PDX in athymic nude mice (NCRNU-F) were treated with 2-cycles of TMZ (40mg/kg/day for 5 days in a 21-day cycle) or with vehicle control gavage (n=10/treatment group). Treatment response was measured by log-rank test comparison of Kaplan-Meier survival curves. The untreated controls and TMZ-resistant PDXs succumbed to brain tumor burden immediately after treatment completion. TMZ-responsive GBM-PDX lines and GBM-naïve nude mice developed respiratory dysfunction 3–5 months after TMZ treatment. Histopathological analysis of lung tissue at autopsy revealed multiple foci of papillary adenocarcinoma (negative for human markers) in both lungs, at an incidence of 95% at 280 days in TMZ-treated nude mice, with no evidence of tumors in other organs. GBM-naïve untreated nude mice in the control group did not develop tumors after 1 year. TMZ treatment of severe combined immunodeficiency (SCID) mice resulted in 77% tumor incidence in the thymus and/or lungs in a GBM-PDX line, 3–4 months post-treatment, with a similar incidence for GBM-naïve treated mice, and no tumors observed in control mice after 9 months. These results present additional evidence of the tumorigenic potential of TMZ, particularly in the background of immunodeficiency. The development of lung/thymus tumors in TMZ-responsive GBM-PDX lines is an undesirable confounding factor not previously reported.